2017
DOI: 10.1515/enr-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 polymorphisms seem not to be associated with prediabetes and type 2 diabetes but predispose to diabetic retinopathy; TLR4 polymorphisms in glucose continuum

Abstract: Objectives. Compared to type 1 diabetes, the role of the immune and autoimmune pathogenetic mechanisms is much less studied in the type 2 diabetes. Toll-like receptors 4 (TLR4) have a leading role in infl ammation, insulin resistance, and vascular damage. Th is study aimed to analyze the relationship between the polymorphisms in TLR4 gene and diff erent stages in the glucose continuum from prediabetes to the type 2 diabetes and chronic microvascular complications.Materials and Methods. Th e study included 113 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…Nevertheless, no significant association was observed between TLR4 Asp299Gly gene polymorphism and DN and diabetic neuropathy subgroup (p > 0.05). The studies of Buraczynska et al [ 16 ], Buraczynska et al [ 18 ], and Zaharieva [ 20 ] were consistent with our results, which further confirmed that TLR4 Asp299Gly gene polymorphism was significantly associated with increased risk of DR. Therefore, we can infer that although DR, DN and diabetic neuropathy were included in microvascular complications, there still exists some differences in the pathogenesis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Nevertheless, no significant association was observed between TLR4 Asp299Gly gene polymorphism and DN and diabetic neuropathy subgroup (p > 0.05). The studies of Buraczynska et al [ 16 ], Buraczynska et al [ 18 ], and Zaharieva [ 20 ] were consistent with our results, which further confirmed that TLR4 Asp299Gly gene polymorphism was significantly associated with increased risk of DR. Therefore, we can infer that although DR, DN and diabetic neuropathy were included in microvascular complications, there still exists some differences in the pathogenesis.…”
Section: Discussionsupporting
confidence: 92%
“…We reviewed the titles and abstracts, 773 articles were excluded. By reading the full text to exclude duplicate, non-English, non-Asp299Gly locus, original text cannot obtain genotype and allele frequency excluded 22, 7 articles were initially included [ 15 20 , 24 ]. Through data collation, 1 literature with no mutation in Asp299Gly site was not included in this meta analysis [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-191, which locates in human 3p21.3, has been found to be overexpressed in numerous types of human tumor (18). For example, a high expression of miR-191 has been found in liver, stomach, large intestine, prostate, and breast cancer (19).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that some curcumin analogs directly bind to a TLR4 co-receptor, myeloid differentiation protein 2 and inhibit TLR4 signaling (50,51). TLR4 is implicated in diabetic nephropathy (52,53), retinopathy (54), and cardiomyopathy (55). TLR4 inhibition also prevents HG-induced NF-κB activation and production of inflammatory cytokines (56).…”
Section: Discussionmentioning
confidence: 99%